1978
DOI: 10.1029/rs013i001p00167
|View full text |Cite
|
Sign up to set email alerts
|

Early results from the DNA Wideband satellite experiment—Complex‐signal scintillation

Abstract: A multifrequency (ten spectral lines between VHF and S band) coherent radio beacon is presently transmitting continuously from a 1000‐km, high‐inclination orbit for the purpose of characterizing the transionospheric communication channel. Its high phase‐reference frequency (2891 MHz) permits direct observation of complex‐signal scintillation, and its very stable, sun‐synchronous orbit allows repeated pre‐midnight observations at low latitudes and near‐midnight observations at auroral latitudes. We present here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(187 citation statements)
references
References 14 publications
4
179
0
Order By: Relevance
“…Ever since, there have been a large number of power spectral studies of amplitude scintillations monitored in different parts of the globe [Singleton, 1974;Crane, 1976;Umeki et al, 1977;Fremouw et al, 1978;Franke and Liu, 1983;Bhattacharyya and Rastogi, 1985;Basu et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, there have been a large number of power spectral studies of amplitude scintillations monitored in different parts of the globe [Singleton, 1974;Crane, 1976;Umeki et al, 1977;Fremouw et al, 1978;Franke and Liu, 1983;Bhattacharyya and Rastogi, 1985;Basu et al, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the potential of differential phase measurements has been recognized for some time as an accurate means of medsuring relative and absolute total (integrated) electron content (TEC) (Leitinger et al, 1975). (Fremouw et al, 1978). We conclude that under conditions of weak scattering the diffruction effects in the phase data :an be largely ignored.…”
Section: "Itjmentioning
confidence: 99%
“…A practical way to estimate the GPS carrier phase fluctuation caused by the oscillator, and the VCO is to measure the detrended phase output of the receiver. Fremouw et al (1978) reported weak phase scintillations with magnitude around 0.086 radians. Recent studies of high-latitude scintillations have shown many scintillation activities with phase scintillations with magnitude in similar or even smaller values (Vikram 2011).…”
Section: Ionosphere Scintillation Receiver Performance Requirementsmentioning
confidence: 99%